Study of The Results of Routine Preoperative Blood Tests on Complications in Sectio Caesarea Patients - Fauzan, M. Fauzan Abdallah; Burhan, Asmat; Nova Handayani, Rahmaya (Global Indonesia Health Care (GOICARE), 2024)
Background: Pre-operative evaluations, including laboratory assessments, are critical components of surgical preparation, with cesarean sections being no exception. Despite their importance, prior research suggests that 70-90% of routine pre-operative blood tests are unnecessary and frequently exhibit abnormal findings. Purpose: This study aims to evaluate the outcomes of routine pre-operative blood tests in patients undergoing cesarean sections at Banjarnegara Islamic Hospital. Methods: A descriptive quantitative study with a cross-sectional design was conducted in June 2024. The sample comprised 44 patients selected through convenience sampling. Data were collected by observing and recording the results of routine pre-operative blood tests, including erythrocytes, hemoglobin, hematocrit, leukocytes, and platelets. Findings: The analysis revealed average erythrocyte levels of 3.95 × 10^6/uL, hemoglobin levels of 11.27 g/dL, hematocrit values of 33.06%, leukocyte counts of 12.62 × 10^3/uL, and platelet counts of 250.77 × 10^3/uL. Intra-anesthesia complications were predominantly hypotension (81.8%), while the most common post-anesthesia complication was postoperative nausea and vomiting (54.5%). Conclusions: The findings indicate a significant proportion of routine blood tests fall outside standard reference ranges, though anesthetic complications remain relatively low. These results underscore the need to reassess the necessity of routine blood tests in pre-operative evaluations and highlight potential areas for improving patient outcomes. Recommendations: Future research should explore the clinical implications of these findings and contribute to establishing guidelines for routine pre-operative testing and management of anesthetic complications